Financial fragility, macroeconomic shocks and banks' loan losses: evidence from Europe - Jarmo Pesola (Bank of Finland, 2007)
This paper tests the hypothesis that the more fragile a banking system is, the more likely it is to experience problems when an unexpected shock hits. The empirical framework where this test is conducted is a reduced form model, where macroeconomic factors explain banks' loan losses. The dependent variable is the ratio of net loan losses to lending in a panel comprising the banking sectors of nine sample countries. An econometric model is estimated on pooled annual data mostly covering the period from the early 1980s to 2002. There are three separate explanatory terms. Two of these include a surprise change both in incomes and real interest rates. Both form a separate cross-product term with lagged aggregate indebtedness. The lagged dependent variable is the third explanatory term possibly capturing the feedback effect from loan losses back to the real economy. The underlying macroeconomic account that this paper puts forward is that loan losses seem basically to be generated by strong adverse aggregate shocks under high exposure of banks to such shocks. The model has been used in connection with stress testing in the Bank of Finland.
URN:NBN:fi:bof-20140807303
Keywords: G21; E44; 330; financial fragility; unexpected macroeconomic shock; loan loss; stress test